2022
DOI: 10.31557/apjcp.2022.23.11.3947
|View full text |Cite
|
Sign up to set email alerts
|

LIMCH1 as a New Potential Metastasis Predictor in Breast Cancer

Abstract: Background and objective: High LIMCH1 expression in lung and renal cancer is determined as a favorable prognostic factor. However, prognostic value of LIMCH1 expression in breast cancer has not been studied yet. Therefore, this study was performed to determine the prognostic value of LIMCH1 expression in breast cancer patients. Methods: This retrospective study included 89 patients with invasive breast carcinoma of no special type. These patients referred to Cancer Research Institute of Tomsk National Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Studies showed that it played an important role in ovarian cancer by affecting cell proliferation and tumour sensitivity to therapy ( 34 ). Furthermore, the ARHGEF19 gene located on chromosome 2 and the LIMCH1 gene located on chromosome 13, within each of which we found one SNP ( TIGRP2P33447_rs8841788 and TIGRP2P176993_rs9197628 , respectively), were associated with an increased risk of breast cancer ( 3 , 30 ).…”
Section: Discussionmentioning
confidence: 84%
“…Studies showed that it played an important role in ovarian cancer by affecting cell proliferation and tumour sensitivity to therapy ( 34 ). Furthermore, the ARHGEF19 gene located on chromosome 2 and the LIMCH1 gene located on chromosome 13, within each of which we found one SNP ( TIGRP2P33447_rs8841788 and TIGRP2P176993_rs9197628 , respectively), were associated with an increased risk of breast cancer ( 3 , 30 ).…”
Section: Discussionmentioning
confidence: 84%
“…Of these genes, PTK7, KLK6 and LIMCH1 have interesting links with breast cancer; PTK7 is a catalytically inactive receptor tyrosine kinase in the Wnt signalling pathway, and a PTK7 targeted antibody-drug conjugate has been shown to reduce tumour-initiating cells 52 . Both KLK6 and LIMCH1 expression has been linked to clinical outcome of breast cancer patients 53,54 The signi cant associations observed between DARPP-32 and its downstream targets DKK1 and GRB7 and patient survival, underscore their importance in breast cancer. By using an approach that combines patient and cell line transcriptomics we have identi ed a number of common genes that provides an insight into the molecular mechanisms underlying differential breast cancer prognosis and highlights potential targets for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Among these signature genes, SLC16A12 has been previously reported to have excellent effectiveness and clinical application value in ccRCC ( 23 ). There is an unfavorable association between LIMCH1 protein expression and distant metastasis-free survival in breast cancer ( 24 ). In addition, as well as being a component of exosomes, the GIPC2 paralog plays a key role in WNT signaling pathways associated with tumor progression and was shown to be robustly stimulating the adhesion, invasion, and migration of prostate cancer ( 25 ).…”
Section: Discussionmentioning
confidence: 99%